Unveiling epidithiodiketopiperazine as a non-histone arginine methyltransferase inhibitor by chemical protein methylome analyses. Issue 66 (31st July 2018) - Sohtome, Yoshihiro; Shimazu, Tadahiro; Barjau, Joaquin; Fujishiro, Shinya; Akakabe, Mai; Terayama, Naoki; Dodo, Kosuke; Ito, Akihiro; Yoshida, Minoru; Shinkai, Yoichi; Sodeoka, Mikiko
Abstract : We present a chemical methylome analysis to evaluate the inhibitory activity of small molecules towards poorly characterized protein methyltransferases. Abstract : We present a chemical methylome analysis platform to evaluate the inhibitory activity of small molecules towards poorly characterized protein methyltransferases (PMTs), facsilitating to identify syn -HyPA-ETP-2 as a non-histone arginine methyltransferase inhibitor.